Determinants of inefficiency in shrimp aquaculture under environmental impacts: Comparing shrimp production systems in the Mekong, Vietnam. Issue 5 (26th January 2022) - Le, Ngan Thi Thanh; Hestvik, Eivind Brækkan; Armstrong, Claire W.; Eide, Arne
Abstract: Shrimp aquaculture systems vary from primitive (extensive/improved extensive) to more industrialized (intensive/semi‐intensive) farms, and the impacts of environmental shocks may differ between them. This article applies the Cobb–Douglas stochastic production frontier function to evaluate the determinants that impact the inefficiency of these intensive and extensive systems in Vietnam. Data is from a survey of 436 white‐leg shrimp ( Litopenaeus vannamei ) farms in the Mekong Area. Our findings show that farmers with self‐reported experiences of drought have higher production efficiency, while experiences of irregular weather reduce efficiency. In addition, education and feeding practice/stocking density adjustment measures increase extensive efficiency. Furthermore, longer crop duration impacts the two systems differently, increasing intensive farm efficiency but decreasing extensive farm efficiency. Interestingly the efficiency effects differ for the two technologies, with two exceptions; efficiency increases for both locations further from the sea and decreases with disease occurrence.